THE CONCEPT OF AN UNMANNED AIRPORT TUG AS AN ALTERNATIVE TO TRADITIONAL AIRCRAFT TUGS - Білякович, Олег; Харченко, Олена (Modern engineering and innovative technologies, 2023)
The article is devoted to the analysis of a conceptual aircraft towing system through the possible implementation of unmanned airport tugs for mass use in busy airports around the world. It is shown that reliable automated aircraft towing systems will co